Implementasi Kurikulum dengan Pendekatan Berbasis Deep Learning di SMPN 2 Kota Bengkulu - Tantri Munirul Amin; Desy Eka Citra Dewi; M. Ilham Gilang (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Education in Indonesia is undergoing a transformation through the Merdeka Curriculum, which requires students to possess 21st-century skills. The Deep Learning method has become an essential approach because it fosters deep conceptual understanding, critical thinking, and reflective student engagement. This study aims to examine the implementation, supporting and inhibiting factors, and the impact of applying Deep Learning at SMPN 2 in Bengkulu City. This study employed a descriptive qualitative approach. Data collection was conducted through in-depth interviews, direct observation, and documentation. The research sample focused on key informants involved in the school ecosystem, namely the Principal, Subject Teachers, 7th and 8th-grade students, and the Vice Principal for Curriculum at SMPN 2 Bengkulu City. Data analysis was conducted interactively and validated through triangulation techniques. This study identified three key findings. First, the implementation of Deep Learning has been successfully integrated into the planning, implementation, and evaluation stages of learning by utilizing problem-based and project-based models, as well as digital technology. Second, its implementation has been supported by school leadership policies and student motivation, but was temporarily hindered by limited resources, time constraints, and uneven teacher understanding. Third, this approach has had a significant positive impact on improving Higher-Order Thinking Skills (HOTS), independence, digital literacy, and the quality of learning interactions. The implementation of Deep Learning has proven highly effective in supporting the successful implementation of the Merdeka Curriculum. Consequently, educational institutions and stakeholders need to engage in ongoing collaboration to strengthen educators’ competencies and digital infrastructure in order to realize adaptive learning focused on 21st-century competencies.